THE EFFECT OF FLUID SATURATION IN AN ANISOTROPIC MULTI-SCALE EQUANT POROSITY MODEL - Chapman M.; Maultzsch S.; Liu E.; Li X.Y. (My University, 2003)
It is recognised that exchange of fluid between fractures and the rock matrix can have a strong impact on a rock's anisotropic elastic properties. A recent theoretical advance considers the effect of the scale length of the fractures. We show that under certain circumstances, this model can be simplified. The simplified model matches laboratory data. A prediction of the model is that frequency-dependent effects are important for fluid substitution in the anisotropic case.
Keywords: ANISOTROPIC; SATURATION; EQUANT